Gore-Tex Medialisation Thyroplasty for Unilateral Vocal Cord Palsy: A Tertiary Centre 7 Years Experience - NPS, Dayangku; MB, Marina; A, Mawaddah; WP, Sharifa Ezat; S, Abdullah (IIUM Medical Journal Malaysia, 2016)
Background: The resultant dysphonia and aspiration in unilateral vocal cord palsy can be overcome with medialisation thyroplasty. With this background, we aim to determine the aetiology of the unilateral vocal cord palsy and effectiveness of the phonosurgical procedure with Gore-Tex as a sole treatment. Methods: Within a seven year period, 37 Gore-Tex medialisation thyroplasty were performed for unilateral vocal cord palsy at our institution and medical records were retrospectively reviewed. Results: There were 18 males and 19 females with mean age of 48.7 years (range 19–81 years). The predominant aetiology was thyroidectomy (43.2%) with benign thyroid disease predominates (n=13) over thyroid malignancy (n=3). Voice outcome was evaluated subjectively using visual analogue scoring system, results indicating that Gore-Tex medialisation thyroplasty was effective in addressing dysphonia in 62.5% (n=15) patients. However it alone cannot address aspiration seen in those with high vagal nerve lesion. Airway compromise occurred in two cases postoperatively (5.4%) presenting as acute stridor. Conclusion: In unilateral vocal cord palsy, Gore-Tex medialisation thyroplasty can effectively improve the resultant dysphonia and often accompanying aspiration which would otherwise be disabling for the patients.